Periodontal Disease: A Covert Source of Inflammation in Chronic Kidney Disease Patients - Gener Ismail; Horia Traian Dumitriu; Anca Silvia Dumitriu; Fidan Bahtiar Ismail (International Journal of Nephrology)
The prevalence of atherosclerotic complications (myocardial infarction, stroke, and sudden death) is increased in end-stage renal disease (ESRD) patients, especially in haemodialysis patients. Increasing evidence suggests that both in general population and in dialysis patients, systemic inflammation plays a dominant role in the pathogenesis of atherosclerotic complications. In general population, also, evidence shows that moderate to severe periodontitis can contribute to inflammatory burden by increasing serum CRP levels and may increase the prevalence of atherosclerotic events. Moreover, the results of some new interventional studies reveal that effective phase I periodontal therapy may decrease serum CRP levels, the most important acute phase protein, monitored as a systemic marker of inflammation and endothelial dysfunction as well, used as an initial predictor of atherosclerotic events. Considering that moderate to severe periodontal diseases have a higher prevalence in CKD and in dialysis population and that periodontal examination is not part of the standard medical assessment, destructive periodontitis might be an ignored source of systemic inflammation in end-stage renal disease patients and may add to the chronic inflammatory status in CKD.